A novel method for the prediction of focal wavefront origins in cardiac arrhythmias. (1st November 2018) - Saluja, Deepak; Kassotis, John; Kostis, William J.; Coromilas, James
Abstract: Background: Current techniques for mapping and ablating cardiac arrhythmias are valuable, but have limitations. We devised a novel method of predicting the origin of a focal arrhythmia wavefront that utilizes conduction velocity ( CV ), the difference in electrogram timing during arrhythmia ( t ), and the distance between two points (z) to generate prediction curves which can be applied to an electroanatomic map. The intersection of two such curves predicts the origin of the wavefront. Objective: To describe the rationale behind a novel method of arrhythmia mapping and assess its feasibility in a retrospective study of focal arrhythmias. Methods: We retrospectively studied 12 patients with arrhythmias with focal chamber activation that were successfully mapped and treated with ablation. CV during arrhythmia was measured using electroanatomic mapping software. Values for z and t were calculated for two pairs of points. Two prediction curves were generated and superimposed onto the electroanatomic maps. The distance between the intersection of the two curves and the wavefront origin was recorded. The shortest distance between individual curves and the wavefront origin was also measured. Results: Twenty-four curves were successfully generated in 12 patients. The distance from the intersection of two curves and the wavefront origin was 9.2 ± 7.7 mm. The shortest distance between individual prediction curves and the wavefront origin was 5.2 ± 5.2 mm. Conclusions: Wavefront origins may be predicted by a novel method utilizing a limited number of measurements. Further study of this method requires its integration with an electroanatomical mapping system. Graphical abstract: Image 1